(untitled) - Maxwell, John C.; (1947-...) (Singapore, 2011)
You have big dreams and major goals for your life. You want to be a leader, fulfilled and fully realized, always able to take what life throws at you and stretch beyond the status quo. But for some reason, you never quite get there. You just aren't living up to your potential, and you don't know why. Now, America's leadership expert, John Maxwell, gives you the tools you need to Be All You Can Be. In this powerful book filled with easy-to-grasp truths you can put to work right away
Keywords: Success -- Religious aspects -- Christianity